Stylistic Analysis of the Poem “Humanity i love you” By E.E. Cummings - Abdul Majid (University of Chitral Journal of Linguistics and Literature, 2020)
This study deals with stylistic analysis of E.E Cummings’s poem "Humanity i love you". This study is dealt under the level of lexicology, graphology and the parallelism in stylistics. Qualitative method has been applied in the analysis of the poem in which the data are collected from primary, secondary and tertiary sources. The analysis of these features is helpful to comprehend the basic theme of the poem that is completely sarcasm and irony. The first free clause "Humanity i love you" repeats several times ironically in the poem but at the end of the poem this structural repetition is being juxtaposed and parallelized with what the poet actually wants to say “Humanity i hate you”.